Ermenautica delle relazioni interspecifiche - Sergio Marchetti (Archivio Antropologico Mediterraneo)
In this essay, from my experience as an ethnographer-mariner in the Ermenautica project, I initially propose a perspective on the reduction of the dimensions of the sea by comparing wet ontologies (Steinberg, Peters 2019), the reflections on the subjective signification of the oceans (Helmreich 2010, 2019) and the discourse on planetarity regimes in the humanities (Chakrabarty, Latour 2020). Subsequently, focusing on the links between the sea, the sailor's body and the boat, I define a phenomenology of navigation. At the same time, I expand the notion of 'hyperobjects' (Morton 2018) to confine knowledge of oceanic immensities to experiences on the crossing, to reflect on the deterritorialisation of individuals and the 'kinships' that arise between humans and surrounding entities during maritime voyages and boat maintenance. I thus delineate a perspective that shifts from the macro planetary sea, seemingly devoid of human senses and relations, to the sea experienced in its even microscopic effects, the theatre of interspecific bonds and meanings (Helmreich 2010; Sahlins 2018; Haraway 2020).